An unresectable and metastatic intrahepatic cholangiocarcinoma with EML4-ALK rearrangement achieving partial response after first-line treatment with ensartinib: a case report - Huang, Senmiao; Li, Dianhe; Huang, Yongye; Lu, Guojie; Tian, Ying; Zhong, Xuefeng; Zheng, Yating; Huang, Mengli; Huang, Fuxi (Frontiers in Oncology, 2023)
Systemic chemotherapies are the primary treatment options for patients with unresectable and metastatic intrahepatic cholangiocarcinoma (ICC), but the effectiveness of current systemic therapies is limited. The development of targeted-therapy has changed the treatment landscape of ICC, and comprehensive genome sequencing of advanced cholangiocarcinoma patients could be beneficial to identify potential targets to guide individualized treatment. Herein, we reported an unresectable and metastatic ICC patient who detected EML4-ALK rearrangement in peripheral blood, which was later confirmed on tissue-based testing, and achieved partial response (PR) after first-line treatment with ensartinib. This case suggests that the liquid biopsy is of clinical value for unresectable or metastatic ICC, and the discovery of rare molecular targets provides new therapeutically approaches for advanced ICC patients.